TRANSITIONAL JUSTICE AND THE CHALLENGING PURSUIT OF SOCIAL JUSTICE - Kastner, Philipp (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
This article argues that the shortcomings of the currently dominant transitional justice model, which largely ignores considerations of social justice, can be explained by several structural factors within the international legal system. It considers the relatively recent establishment of transitional justice institutions and argues that despite different forms – international criminal tribunals, truth and reconciliation commissions, peoples’ tribunals – these institutions are motivated by similar rationales and have the same underlying objectives. These parallels, enhanced by the both explicit and implicit normative influences that the respective institutions have on each other, and the overly linear notion of time embedded in international law have given rise to a problematic model of transnational transitional justice. Among others, this model hinders the pursuit of social justice beyond a narrow focus on individual human rights and individualized responsibilities for specific crimes. The article calls for a deliberate turn away from prefabricated institutional responses as well as for a much-needed reconceptualization of the prevailing model of justice within international legal discourses in order to address structural inequalities and forms of injustice that are often part of the root causes of armed conflicts.